1992
DOI: 10.1111/j.1365-2044.1992.tb02394.x
|View full text |Cite
|
Sign up to set email alerts
|

An automated system for testing the accuracy of patient‐controlled analgesia devices

Abstract: SummaryA system was developed to test the accuracy of patient-controlled analgesia devices in situations simulating clinical use. Bolus requests are made automatically at predetermined intervals, and the infusate delivered is measured and recorded without the need for operator presence. To ensure clinical relevance, the bolus request times used in this study corresponded to a pattern typical of those requested by patients on the ward. Graseby, Abbott Provider 5.500 and W A C patient-controlled analgesia device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Current recommendations for testing PCA devices [2,4-7] do not include measurements of lockout period and factors which may influence it. One of these studies [4], proposed testing at a maximum demand frequency of only six per hour and would have failed to detect the problem our study has revealed.…”
Section: Discussionmentioning
confidence: 97%
“…Current recommendations for testing PCA devices [2,4-7] do not include measurements of lockout period and factors which may influence it. One of these studies [4], proposed testing at a maximum demand frequency of only six per hour and would have failed to detect the problem our study has revealed.…”
Section: Discussionmentioning
confidence: 97%
“…The system used to test these pumps was a modification of a previously developed computer-controlled system. 4 Activation of bolus requests was made automatically in a pattern designed to simulate requests made by a postoperative patient: in each one hour interval from zero to six demands were made ( Table 1). The system was interfaced to a set of electrically operated pneumatic solenoid valves which delivered piped compressed air, via a regulator, to a "pneumatic thumb" which activated the PCA device.…”
Section: Methodsmentioning
confidence: 99%
“…This system was a modification of one (10) interface was replaced by a set of electrically operated pneumatic solenoid valves that delivered piped compressed air via a regulator to a 20-mL low friction (glass) syringe, which activated the PCA device. A computer-controlled system was used to activate the PCA device using a "pneumatic finger" to press the medication-demand button.…”
Section: Methodsmentioning
confidence: 99%